Robotic pancreaticoduodenectomy for pancreatic head cancer and periampullary lesions. Issue 5 (28th March 2021) - Shyr, Yi‐Ming; Wang, Shin‐E; Chen, Shih‐Chin; Shyr, Bor‐Uei; Shyr, Bor‐Shiuan
Abstract: Pancreaticoduodenectomy, so‐called "Whipple operation, " is a time‐consuming and technically demanding complex operation. Traditionally, this procedure has been performed most usually by open approach, which results in a large and painful wound. With the introduction of laparoscopic and robotic surgery, minimally invasive surgery (MIS) has emerged as a worldwide trend to improve wound cosmesis and to minimize wound pain. Although MIS for pancreaticoduodenectomy has also been attempted at some centers, the role of MIS, either robotic or laparoscopic approach, has not been well‐established for complex pancreaticoduodenectomy. Given that laparoscopic pancreaticoduodenectomy has been limited by its technical complexity and the high level of advanced laparoscopic skills required for pancreatic reconstruction, a robotic surgical system is introduced to overcome several limitations related to the laparoscopic approach. Providing high‐quality three‐dimensional (3‐D) vision, high optical magnification, articulation of robotic instruments, greater precision with suture targeting, and elimination of surgeon tremor, robotic surgical systems innovatively perform more delicate and complex procedures involving extensive dissection and suturing techniques such as pancreaticoduodenectomy. Although associated with longer operative time, robotic pancreaticoduodenectomy (RPD) has been claimed to have the benefits of less delayed gastric emptying, less blood loss, shorter length of postoperative stay, and lower wound infection rate, as compared with the traditional open pancreaticoduodenectomy (OPD). Moreover, RPD seems to be not only technically feasible but also justified without compromising the survival outcomes for pancreatic head and ampullary adenocarcinomas. Therefore, RPD could be recommended not only to surgeons but also to patients in terms of surgical feasibility, surgical outcomes, and patient satisfaction. Abstract : Robotic approach allows surgeons to perform more complicated and delicate procedures such as pancreaticoduodenectomy involving extensive dissection and restoration of digestive tract continuity for the pancreas, bile duct, and gastrointestinal tract. Robotic pancreaticoduodenectomy has been reported as associated with less blood loss, less delayed gastric emptying, shorter length of postoperative stay, and lower wound infection rate, but longer operative time, as compared with the traditional open pancreaticoduodenectomy.